Seven new species of the genus Xestoleberis (Ostracoda: Podocopida: Cytheroidea) from the Fiji Archipelago - Chand, Prerna; Kamiya, Takahiro (Zootaxa, 2016)
The genus Xestoleberis has a global distribution, and although they are predominant in shallow marine environments adapted to both sediment and algal habitats, only two species of this genus, Xestoleberis curta (Brady, 1866) and Xestoleberis variegata Brady, 1880, have previously been reported from the Fiji archipelago. Herein we report seven new species of the genus Xestoleberis from intertidal environments of fringing reef flats of the Fiji Islands: Xestoleberis becca n. sp., Xestoleberis concava n. sp., Xestoleberis gracilariaii n. sp., Xestoleberis marcula n. sp., Xestoleberis natuvuensis n. sp., Xestoleberis penna n. sp. and Xestoleberis petrosa n. sp. With the exception of X. becca n. sp., Xestoleberis species show restricted distribution within Fijian waters. The possible causes for their distribution patterns are suggested to be physical barriers imposed by the fast flowing Bligh Water currents, and islands separated by deep ocean waters.